Prioritizing a global research and policy agenda for Betel Quid (BQ) and Areca Nut (AN) - Mark Parascandola; Hedieh Mehrtash; Amara Ndumele; Kalina Duncan (Tobacco Induced Diseases, 2018)
Background and challenges to implementation BQ/AN use is prevalent among approximately 600 million people globally and, is a risk factor for oral and esophageal cancers. It has also shown effects on the cardiovascular, nervous, GI and metabolic, respiratory, and reproductive systems. Research is needed to understand and implement effective prevention and control of BQ/AN, screening and treatment for related cancers, policy, and economic impacts.